Analisis Tipe Teks Rekon pada Teks Berita Media Center Kota Bengkulu - Oktarina Widarsih (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2021)
The purpose of this study is to find out the structure and linguistic aspects of recon text type in the online news text of Media Center Bengkulu issued in December 2019. This research uses descriptive method with qualitative approach. The data in this study is 60 news texts. The data source is media centre online site of Bengkulu https://mediacenter.bengkulukota.go.id. issue of December 2019. Based on the analysis of the structure and linguistic aspects of the type of recon text found the recon structure used by the author of online news Media Centre Bengkulu, namely the recon structure used by the author of online news Media Centre Bengkulu city did not meet the criteria of factual recon text, due to the description of the event that is the core of the text, the tendency of the author to only relay back the ujuran from the source of the event description, but to answer